Morphological variation within Solanum campylacanthum (Solanaceae) in Uganda and its relationship with S. cerasiferum - Kawuma, Carol; Namaganda, Mary; Katuura, Esther; Ipulet, Perpetua; Mulumba, John Wasswa; Kakudidi, Esezah; Tusiime, Felly Mugizi; Bello, Anifat Olayemi; Stedje, Brita (Phytotaxa, 2024)
This is a morphological study of 108 accessions of Solanum campylacanthum and 10 accessions of Solanum cerasiferum. The aim was to assess the morphological variations that occur within the S. campylacanthum species in Uganda and evaluate the morphological differences between S. campylacanthum and S. cerasiferum. Fourteen quantitative and eleven qualitative vegetative characters were measured and analysis done by phenetics method. Cluster (UPGMA) and box plot analyses were done in PAST program version 4.03. Prickle density and leaf tip angles are reported for the first time as being useful in the intraspecific delimitation of S. campylacanthum. The distinction between S. cerasiferum and S. campylacanthum can only be based on leaf base shapes, which is, attenuate and oblique respectively.